Análise dos custos de produção e da rentabilidade do cultivo de guaraná: um estudo de caso no sul do estado do Amazonas - Albuquerque, Roberto Torres (Brasil, 2025)
Guarana (Paullinia cupana Kunth) is a plant native to the Amazon, originally cultivated by indigenous peoples. Currently, the state of Bahia leads national production, followed by Amazonas, with emphasis on the municipalities of Maués and Urucará. Widely sold in the domestic and foreign markets, guarana has economic relevance in Brazil, especially for family farmers. This study aimed to identify and analyze the production costs and profitability of guarana cultivation in the São Francisco Settlement, in the municipality of Canutama-AM, located 58 km from Porto Velho-RO. The research adopted a qualitative-quantitative approach, including a literature review, exploratory research, and interviews with a family farmer. Production costs were calculated according to the Conab methodology (2024). The results indicated that, although guarana production guarantees the livelihood of some families and demonstrates profitability, the net profit margin is small, requiring greater management, investments, and public policies to increase its economic viability. In the municipality of Canutama, the main production costs are related to labor, and production is still modest compared to other regions of Amazonas and Bahia. However, the data demonstrate the economic potential of the activity, and this study is an initial basis for future research on the guarana production chain. In addition, it can support institutions such as Idam, reinforcing the importance of this crop in the daily life of southern Amazonas.